Tindak Pidana Pemerkosaan Yang Dilakukan Ayah Kandung Terhadap Anak - Sindhi Maria Angini Pattiasina; Margie Gladies Sopacua; Denny Latumaerissa (Faculty of Law Universitas Pattimura, 2023)
Rape is a very heinous, immoral and despicable crime and violates the norm whereby the victims are women, both adults and minors. The perpetrators of the criminal act of rape are often people who are known by the victim and some even have family relations and what is most concerning is a father who has the heart to rape his own biological child (incest). Purposes of the Research: to examine and analyze the factors that cause biological fathers to commit criminal acts of rape against children and efforts to deal with criminal acts of rape for children who experience criminal acts of rape. Methods of the Research: The type of research used in this study is normative juridical. The sources of legal materials are primary and secondary legal materials. Data collection techniques are carried out through identification of laws and regulations, legal journals, books.Results of the Research: Factors that cause the biological father to commit the crime of rape are low education and economic factors, lack of trust in the law, environment and residence, alcohol and lack of understanding of and efforts to counteract the crime of rape for children who have experienced the crime of rape is through the use of penal means, namely through criminal law, this effort is related to the implementation of legal rules and the enforcement of legal rules. Other actions using non-penal means, namely eradicating the circulation of pornographic videos, places that are usually used as tools for pornographic activities and holding outreach to the community and to schools about current sex education.